PEMBELAJARAN VAN HIELE DENGAN MEDIA KERTAS ORIGAMI DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA - Ida Wardatul Akmalia (FKIP Unirow Tuban, 2018)
This research is motivated by the low level of mathematics learning outcomes of fourth grade students of SDN Kanor II in the learning process can be known through students' test scores, there are still many students who have not been completed. This is because learning is still teacher-centered. To overcome this problem, the author uses the Van Hiele learning model with Origami Paper media to improve students' mathematics learning outcomes.This study uses classroom action research. Each cycle consists of four stages, namely planning, action, observation, and reflection. Research instruments in data collection were carried out through test sheets, observation sheets, and questionnaire sheets. The subject of the study was the fourth grade students of SDN Kanor II with 11 students. Improving learning outcomes is shown from classical completeness of 27.27% in pre cycle to 63.63% in cycle-1 and 100% in cycle-2. Teacher activity is 72.5% in cycle-1 to 92.5% in cycle-2. The response of students to the Van Hiele learning model with Origami Paper media gave a positive response from each proven cycle the average percentage of total answers TS 4.04% in cycle-1 and 2.02% in cycle-2.